(untitled) (Journal of the Spanish Institute for Strategic Studies, 2020)
One of the aspects that most affects maritime security is, undoubtedly, the proper establishment of borders between border States, to the extent that once determined, each one has clear the extent of their respective jurisdiction. This facilitates navigation for third States to eliminate the tension that is generated when two or more States claim the same maritime space. At the same time, they have the certainty of what is the norm that must be respected according to the waters that are going through at every moment. The entry into the scene of the 1982 Sea Law Convention, with new spaces and extensions has generated some complication on this issue. This has a special impact on Africa, the continent with the largest number of coastal States. The objective of this study is to explain which African maritime boundaries are definitively fixed - by agreement or by international judgment-, in order to have a certain and up-to-date knowledge of the areas that enjoy stability in the matter and, by exclusion, which are still outstanding. At the same time, to know the maritime borders already established and the criteria that have been applied to fix them, can constitute an important reference and help for the rest of African states that still have their delimitations pending.